Adult Dermatomyositis with Bleeding Ulcer in the Pharynx - Junko Kusano; Yuka Takahashi; Yoshikata Misaki; Norihiko Murai (Case Reports in Otolaryngology)
Dermatomyositis (DM) is one of the idiopathic inflammatory myopathies caused by complement-mediated vasculopathy or vasculitis in the muscle. Although the gastrointestinal (GI) mucosa has been reported to be involved as a result of vasculitis or vasculopathy, ulceration in the pharynx is a rare manifestation of DM. A 54-year-old woman complaining of muscle weakness in the extremities, low-grade fever, and dysphagia was diagnosed as having DM. Despite medical treatment with corticosteroids and immunosuppressive agents, her DM progressed rapidly, leading to exacerbation of the dysphagia. About 3 weeks after undergoing tracheostomy as a preventive measure against aspiration, the patient developed intractable respiratory tract hemorrhage. Repeated laryngoendoscopy revealed a bleeding ulceration in the pharynx that required hemostasis with electric cautery under general anesthesia. No bleeding recurred thereafter. Histopathologically, the pharynx exhibited nonspecific inflammatory cell infiltration in the muscle tissue. This rare manifestation may be considered in cases of DM with unexplainable airway bleeding.